EVALUASI KEBUTUHAN AIR IRIGASI DENGAN APLIKASI CROPWAT 8.0 DAERAH IRIGASI AMPING PARAK - Dasril Dasril; Bambang Istijono; Nurhamidah Nurhamidah (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2021)
The prediction of water requirement is important in planning and managing irrigation system. Based on this case, this study aims to evaluate water requirement of irrigation to obtain the prediction of maximum value of water requirement. The research took place in Irrigation Area of Ampiang Parak at Pesisir Selatan Regency with the area was 2,363 hectares. The descriptive qualitative analysis approach was used to collect the data by using observation, interview and taking of primer and secondary data. The tabulation of data used Cropwat version 8.0 software to analyze water requirement values. The result of this research the calculation of water requirement values using Cropwat version 8.0 software are 4.772 m3/sec in MT 1, 4.770 m3/sec in MT 2, and 5.05 m3/sec in MT 3. The data shows that irrigation area may not have dryness. However, there is some area that is rainfed. Based on observation at Irrigation Area of Amping Parak there are leaking lines, and there are area irrigations that have not connected according to irrigation area of Amping Parak scheme.